Cross Currents in Protein Misfolding Disorders: Interactions and Therapy - Morales, Rodrigo; Green, Kristi M.; Soto, Claudio (CNS & Neurological Disorders - Drug Targets, 2009)
Protein Misfolding Disorders (PMDs) are a group of diseases characterized by the accumulation of abnormally folded proteins. Despite the wide range of proteins and tissues involved, PMDs share similar molecular and pathogenic mechanisms. Several epidemiological, clinical and experimental reports have described the co-existence of PMDs, suggesting a possible cross-talk between them. A better knowledge of the molecular basis of PMDs could have important implications for understanding the mechanisms by which these diseases appear and progress and ultimately to develop novel strategies for treatment. Due to their similar molecular mechanisms, common therapeutic strategies could be applied for the diseases in this group.